2017
DOI: 10.1016/j.matbio.2016.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Nerve Guidance by a Decellularized Fibroblast Extracellular Matrix

Abstract: Spinal cord and peripheral nerve injuries require the regeneration of nerve fibers across the lesion site for successful recovery. Providing guidance cues and soluble factors to promote neurite outgrowth and cell survival can enhance repair. The extracellular matrix (ECM) plays a key role in tissue repair by controlling cell adhesion, motility, and growth. In this study, we explored the ability of a mesenchymal ECM to support neurite outgrowth from neurons in the superior cervical ganglia (SCG). Length and mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
59
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 53 publications
(53 reference statements)
3
59
0
1
Order By: Relevance
“…When neuronal attachment was measured on or in between the ridges, laminin and fibronectin did equally well. The observed enhancement of neuronal outgrowth and guidance associated with laminin is in keeping with several other studies investigating different substrates for neuronal regeneration [6, 13, 35, 38]. ECM proteins or their fragments play an important role in cell adhesion through ligand receptor interactions, and these interactions may be an important component to consider in developing novel biomaterials [39-41].…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…When neuronal attachment was measured on or in between the ridges, laminin and fibronectin did equally well. The observed enhancement of neuronal outgrowth and guidance associated with laminin is in keeping with several other studies investigating different substrates for neuronal regeneration [6, 13, 35, 38]. ECM proteins or their fragments play an important role in cell adhesion through ligand receptor interactions, and these interactions may be an important component to consider in developing novel biomaterials [39-41].…”
Section: Discussionsupporting
confidence: 84%
“…This can be due to the different amount of proteins used or absorbed into the scaffold. Previous studies have demonstrated concentration dependent differences in cell attachment and outgrowth, however, concentrations used in this study were within range of those used in other studies [6, 24, 36, 37]. It is also interesting to note that the DRG outgrowth rate on the fibronectin coated sheets was still increasing at the 24-48 hour time point and may have results in greater outgrowth length at a later time point.…”
Section: Discussionmentioning
confidence: 47%
See 2 more Smart Citations
“…The damaged nervous system has a limited regenerative capacity and therefore poses a considerable therapeutic challenge with no effective treatment available. The limited regeneration is though mainly attributed to the inability to recreate the ECM microenvironment within the disrupted neural tissue in order to induce proper neural differentiation and growth . Therefore, a growing body of work describes the use of decellularized tissues as a novel strategy for nerve regeneration.…”
Section: Applications Of Processed Decm‐based Materialsmentioning
confidence: 99%